Budget Implementation Performance at the Directorate of Prevention and Control of Direct Communicable Diseases within the Ministry of Health - Gustia Rakhmanita; R. Luki Karunia; Neneng Sri Rahayu (International Journal of Economics Development Research (IJEDR), 2023)
Budget implementation is a manifestation of government programs and activities that have been planned, which have been assessed since 2014 by the Ministry of Finance, by setting Budget Implementation Performance Indicators (IKPA). based on the IKPA scores of the Directorates of prevention and control of directly Infectious Diseases of the Ministry of Health in 2019 – 2021 it was not in a good category, so research was carried out regarding the factors that influence budget execution performance and strategies to improve budget execution performance. This study uses a descriptive method with a qualitative approach, data collection techniques through interviews, observation and document review, the theory used is performance appraisal, capacity building, accountability and management control. The results of the research supporting factors are the availability of laptops and Internet network. Inhibiting factors are planning factors that are not mature enough, lack of discipline in budget execution, lack of firm leadership commitment. The 3 priority strategies are Increasing leadership oversight, improving coordination and providing accountability reports to leaders. the five strategies in the long term are providing technical guidance, developing standard operating procedures, creating an internal system, looking at work unit information systems that excel, sanctions for negligent employees. The conclusion for this study is that the supporting factors are due to the availability of facilities and infrastructure, the inhibiting factors are due to the lack of compliance in implementing the budget, while the the suggestion for this research is to update the supporting factors for facilities and infrastructure every year, for the inhibiting factors the leadership must cross check for each activity, improve coordination vertically to superiors and horizontally to fellow budget management staff, so that the strategy can b implemented requires a strong commitment from the leadership to align planning with budgeting, guidance is needed for finance management, planners in budget execution.